Advances in Life Cycle Engineering for Sustainable Manufacturing Businesses [electronic resources]: Proceedings of the 14th CIRP Conference on Life Cycle Engineering, Waseda University, Tokyo, Japan, June 11th-13th, 2007 - CIRP International Conference on Life Cycle Engineering (14th : 2007 : Waseda University); Takata, Shozo; Umeda, Yasushi; SpringerLink (Online service) (London : Springer-Verlag London Ltd, 2007)
22